Congenital cleft earlobe repair by triangular flap technique - Kuldeep Singh; Krittika Aggarwal; Meenu Beniwal (Wolters Kluwer Medknow Publications, 2022)
Introduction: Congenital cleft earlobe is a common congenital deformity of earlobe. Various techniques have been described for its repair, but cosmetic deformity usually persists. We present our result using triangular flap repair for simple longitudinal cleft of earlobe. Materials and Methods: The procedure was done in five cases who presented between 2017 and 2020. The technique uses the same principles as in Randall-Tennison triangular flap repair for cleft lip. Results: Earlobes were near-symmetrical, postoperative scar minimal and patient satisfaction was very good in all cases. Ear piercing was done without any complications at least 6 months after surgery. After a follow-up of 1 year, no complications were noted. Conclusions: Triangular flap repair technique for cleft earlobe follows the principles of Randall-Tennison triangular flap repair for cleft lip. It provides very good results with esthetic contour, minimal scar with no complications in case of simple longitudinal cleft.